Biomimetics in Medicine and Pharmacy - New Perpectives Should be Strengthed - Thanh Hai, Nguyen; Tung, Bui Thanh; Hue, Pham Thi Minh (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2017)
Biomimetics (or bionics) is a highly attractive scientific field. It has a great impact on almost every aspect of life, from the development of consumer devices on the basis of classical mechanical principles to modern fields like robot, electronic chip, nano technology… In the field of medicine and pharmacy, biomimetic methods are of great value in developing drugs, developing methods for the diagnosis, prevention and treatment diseases. The application of biomimetics in the field of medicine and pharmacy is a promising prospect in terms of superiority, feasibility and sustainability. The consideration and application of the biomimetic methods will undoubtedly generate new advances not only in current methods, but also in the improvement of existing methods. In the field of drug development, the study of the biological world in order to find new pharmaceutical raw materials and new effective action is a feasible and highly effective method. The solution to major problems of pharmaceutical science, such as releasing drugs in the right place, at the correct dose and in time, will certainly find a better way by using the data of nature. Formation and promotion of biomimetic - pharmaceutics can be a new direction for new advances in health sciences. Keywords Biomimetics; Bionics; Biomimetic - pharmaceutics; Biological system References [1] Vincent Julian Fv, Bogatyreva Olga A, Bogatyrev Nikolaj R, Bowyer Adrian, Pahl Anja-Karina. Biomimetics: its practice and theory. Journal of the Royal Society Interface 3(9) (2006) 471. [2] Hwang Jangsun, Jeong Yoon, Park Jeong Min, Lee Kwan Hong, Hong Jong Wook, Choi Jonghoon. Biomimetics: forecasting the future of science, engineering, and medicine. International journal of nanomedicine 10((2015) 5701. [3] Valko Klara. Physicochemical and biomimetic properties in drug discovery: chromatographic techniques for lead optimization. John Wiley & Sons (2013). [4] Bar-Cohen Yoseph. Biomimetics-biologically inspired technologies CRC Press. Boca Raton(2006). [5] Nguyễn Thị Thanh Thủy, Trịnh Ngọc Dương, Nguyễn Thị Thanh Bình, Bùi Thanh Tùng, Nguyễn Thanh Hải. Chất vận chuyển oxy Perfluorocarbon và triển vọng phát triển hồng cầu nhân tạo,. Tạp chí Khoa học Đại học Quốc gia Hà Nội - Khoa học Y Dược, 32(2) (2016) 1 [6] Từ Minh Koóng, Nguyễn Thanh Hải. Thuốc tới đích. Tạp chí Dược học 388(8) (2008) 1. [7] Từ Minh Koóng, Nguyễn Thanh Hải. Thuốc tới đích. Tạp chí Dược học 389(9) (2008) 2. [8] Gorb Stanislav N. Biological attachment devices: exploring nature's diversity for biomimetics. Philosophical Transactions of the Royal Society of London A: Mathematical, Physical and Engineering Sciences 366(1870) (2008) 1557. [9] Từ Minh Koóng, Nguyễn Thanh Hải. Công nghệ nano và sản xuất dược phẩm. Tạp chí Dược học 369(1) (2007) 2. [10] Từ Minh Koóng, Nguyễn Thanh Hải. Công nghệ nano và sản xuất dược phẩm. , Tạp chí Dược học 370(2) (2007) 3. [11] Từ Minh Koóng, Nguyễn Thanh Hải. Công nghệ nano và sản xuất dược phẩm. Tạp chí Dược học 371(3) (2007) 4. [12] Phạm Thị Minh Huệ, Nguyễn Thanh Hải, Võ Xuân Minh. Phytosome: Giải pháp tăng sinh khả dụng cho các hoạt chất có nguồn gốc dược liệu. Tạp chí Dược học 465(1) (2015) 2.